Revitalisasi Ikon Perbatasan Desa sebagai Media Branding Wilayah Pedesaan: Pengabdian - Ilma Nur Rizqi; M. Umar Faqieh; Muammar; Abdul Khamid; Yulia Feriska (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Poorly maintained border monuments have not been able to represent village identity as a symbol of pride. This program aims to revitalize the monument as a rural branding medium to strengthen visual identity and increase community participation. The method uses a participatory approach involving village officials, youth organizations, and residents, with stages of observation, volume calculation, cleaning, painting, acrylic installation, and evaluation. Success is measured by the physical changes to the monument, community involvement, and community response. The results show significant aesthetic and symbolic changes, with high participation in cleaning (80%) and painting (70%), although lower participation in acrylic installation (60%) and evaluation (50%). The revitalization not only improves the physical appearance but also increases collective pride, sparks initiatives to expand the program to other public facilities, and has proven effective as a community-based rural branding strategy.